Dung beetle assemblages (Coleoptera, Scarabaeinae) in Atlantic forest fragments in southern Brazil - Campos,Renata C. (2013)
Dung beetle assemblages (Coleoptera, Scarabaeinae) in Atlantic forest fragments in southern Brazil. The beetles of the subfamily Scarabaeinae are important organisms that participate in the cycle of decomposition, especially in tropical ecosystems. Most species feed on feces (dung) or carcasses (carrion) and are associated with animals that produce their food resources. Dung beetles are divided into three functional groups: rollers, tunnelers and dwellers. This present work aims to study the diversity of dung beetle communities inhabiting fragments of the Atlantic Forest, with the purpose of describing the ecology of the species in southern Brazil. This study was conducted in the region of Campos Novos, in Santa Catarina, where twenty sites of Atlantic forest fragments were sampled. Samplings of dung beetles were conducted using 200 pitfall traps, of which 100 were baited with human feces and another 100 with carrion. Size and environmental complexity were also measured for each forest fragment. A total of 1,502 dung beetles, belonging to six tribes, 12 genera and 33 species, were collected. Results of the Levin's index of niche breadth indicated that 11 species were categorized as being coprophagous, ten as generalists, and two as necrophagous. Most species are tunnelers (19), nine of rollers and four of dwellers. The great diversity of Scarabaeinae in the region of Campos Novos, including several rare species, adds important data to the Scarabaeinae fauna in the central-western region of Santa Catarina. It may also help choosing priority areas for conservation in the region, where human impact, with large areas of monoculture, increasingly threatens the fragments of Mixed Ombrophilous Forest.